Harmoni Agama di Desa Tewang Darayu: Menguatkan Moderasi Beragama untuk Membangun Persatuan - Rinto Hasiholan Hutapea; Sri Angellyna; Sharon Michelle O. Pattiasina; Anggita Deodora Siten; Fernando Dorothius Pongoh; Isabella Jeniva (Real Coster : Jurnal Pengabdian kepada Masyarakat, 2024)
Community Service Activities were carried out in Tewang Darayu Village, Pulau Malan District, Katingan Regency. This activity aims to be a form of strengthening religious moderation for the community in Tewang Darayu village. This strengthening can increase the awareness of the Tewang Darayu village community in building harmonious relations between religions. Apart from that, it can strengthen the spiritual aspect of religion among the community as a whole as part of efforts to maintain religious moderation which is born from the diverse realities of life in Tewang Darayu village. This activity uses the Asset Based Community Development (ABCD) method by emphasizing the strengths possessed by the Tewang Derayu village community. The impact obtained from this activity is that the Tewang Derayu village community experienced increased knowledge and were able to implement Religious Moderation indicators in socio-cultural dynamics based on a humanist attitude to life. Apart from that, Tewang Derayu village can also be a model model for surrounding villages in implementing the values of Religious Moderation. Keywords: religious moderation; strengthening; religious relationsAbstrakKegiatan Pengabdian Kepada Masyarakat dilaksanakan di Desa Tewang Darayu, Kecamatan Pulau Malan, Kabupaten Katingan. Kegiatan ini bertujuan untuk sebagai bentuk penguatan moderasi beragama bagi masyarakat di desa Tewang Darayu. Adapun penguatan ini dapat meningkatkan kesadaran masyarakat desa Tewang Darayu dalam membangun harmoni hubungan antar agama. Selain itu, dapat memperkuat dimensi aspek spiritual dalam beragama di antara masyarakat secara keseluruhan sebagai bagian dari upaya untuk menjaga moderasi beragama yang lahir dari realitas kehidupan yang beragam di desa Tewang Darayu. Kegiatan ini menggunakan metode Asset Based Community Development (ABCD) dengan menekankan pada kekuatan yang dimiliki oleh masyarakat desa Tewang Derayu. Dampak yang diperoleh dalam kegiatan ini yaitu masyarakat desa Tewang Derayu mengalami peningkatan pengetahuan serta mampu mengimplementasikan indikator-indikator Moderasi Beragama dalam dinamika sosial budaya yang didasarkan pada sikap hidup humanis. Selain itu, desa Tewang Derayu juga dapat menjadi model percontohan bagi desa-desa sekitar dalam implementasi nilai-nilai dari Moderasi Beragama.Kata Kunci: moderasi beragama; penguatan; relasi agama